2016
DOI: 10.1007/s10488-016-0755-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Studies on the System-Wide Implementation of Evidence-Based Psychotherapies for Posttraumatic Stress Disorder in the Veterans Health Administration

Abstract: Since 2006, the Veterans Health Administration (VHA) has instituted policy changes and training programs to support system-wide implementation of two evidence-based psychotherapies (EBPs) for posttraumatic stress disorder (PTSD). To assess lessons learned from this unprecedented effort, we used PubMed and the PILOTS databases and networking with researchers to identify 32 reports on contextual influences on implementation or sustainment of EBPs for PTSD in VHA settings. Findings were initially organized using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 84 publications
8
124
1
Order By: Relevance
“…In fact, VA leadership has already adopted this facilitation strategy to support implementation of PC-MHI, as well as other policy-mandated evidence-based innovations, at facilities across VA that struggle to implement new programs [9, 10, 15, 75]. Based on experiences of facilitators in this study, we developed IF training materials and the external expert facilitator (JEK) and one of the internal regional facilitators have been training clinical operations personnel in these methods [76, 77].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, VA leadership has already adopted this facilitation strategy to support implementation of PC-MHI, as well as other policy-mandated evidence-based innovations, at facilities across VA that struggle to implement new programs [9, 10, 15, 75]. Based on experiences of facilitators in this study, we developed IF training materials and the external expert facilitator (JEK) and one of the internal regional facilitators have been training clinical operations personnel in these methods [76, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes mandates are poorly implemented because they receive little national implementation support [13, 14]. On the other hand, even when mandated EBPPs are highly supported, implementation can still be variable; this has been the case for several VHA programs including suicide prevention [11] and evidence-based psychotherapy treatments [9, 15]. VHA has also invested significant resources in its PC-MHI initiative [10].…”
Section: Introductionmentioning
confidence: 99%
“…Olin and colleagues (this issue) investigate outer context and inner context factors that predicted clinician drop out from a statewide training on an EBP in the State of NY, finding that younger clinicians and those that practiced in upstate-rural areas were less likely to drop out from training in an EBP. Finally, Rosen and colleagues (this issue) present a review of research focusing on the implementation of two EBPs for PTSD in the U.S. Department of Veterans Affairs. The article serves as one model of how we can learn across multiple implementation efforts that focus on specific EBPs and settings.…”
Section: Brief Summary Of Articlesmentioning
confidence: 99%
“…Specifically, some of the most successful endeavors to ensure uptake and use of treatment protocols have involved policy changes and support from the top-down, with leaders and administrators pushing for adoption of such treatments in their organizations. Specifically, less centralized and more local clinics within these larger health care systems are less likely to show adoption and use of such evidence-based protocols if there is no prioritization or provision of resources for such treatments (Rosen et al, 2016). However, even with such a large-scale, top-down approach, penetration of front-line protocol treatments such as PE and CPT has been found to be low in some VHA settings (Sayer et al, 2017).…”
Section: Systems-level Infrastructurementioning
confidence: 99%
“…For example, the VHA roll-out of EBPs for PTSD (i.e., PE and CPT) has resulted in significantly more use of these protocols in VHA clinics across the country, and this was largely due to central office leaders who ensured training and ongoing use of these therapies to patients seeking treatment for PTSD (Karlin et al, 2010). For instance, a recently conducted review of 32 studies examining such contextual factors in the VHA setting used the EPIS (exploration, planning, implementation, and sustainment) framework but found that some of the findings (such as adopter beliefs and outcomes of implementation) were better captured using the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) and CFIR (Consolidated Framework for Implementation Research) frameworks (Rosen et al, 2016). Specifically, less centralized and more local clinics within these larger health care systems are less likely to show adoption and use of such evidence-based protocols if there is no prioritization or provision of resources for such treatments (Rosen et al, 2016).…”
Section: Systems-level Infrastructurementioning
confidence: 99%